Perca Endek Sebagai Inspirasi Kolaborasi Pouch Lukis Yang Bernilai Seni Tinggi - Apriliani, Sari; Gulendra, I Wayan; Budiaprilliana, Luh (Program Studi Seni Murni ISI Bali, 2022)
Adding surface designs or paintings to traded products is one way to increase the value of the goods, the value in question is aesthetics and selling price. Agung Bali Collection as a writing partner in MBKM Entrepreneurial activities, provides knowledge about the canting massage technique which can be used as an additional technique in making surface designs. HOLD ME is a form of Start-Up business that the author created personally, this business is engaged in the fashion sector, with canvas bags and endek patchwork as the main raw materials for making strong and environmentally friendly products, as well as the use of endek patchwork in the Agung Bali Collection as a form of cultural preservation and processing of patchwork waste will make goods have high selling power. Until now, HOLD ME has produced six pouch product models and is planning to expand its business. The product that has been produced is a canvas cloth bag in collaboration with endek patchwork and there is a surface design with brush and massage techniques with use of glitter which can create unique, beautiful, and special bag products, consumers not only enjoy the product through visual beauty but also can be enjoyed from the functional or usability aspect of the product.